A mixed methods bibliometric investigation of the World Review of Entrepreneurship, Management and Sustainable Development: from qualitative to quantitative data. (2018) - Marzi, Giacomo; Rialti, Riccardo; Dabi?, Marina; Caputo, Andrea
This article offers a complete overview of the World Review of Entrepreneurship, Management and Sustainable Development (WREMSD) from 2005 to 2015. The article employs an innovative mixed method, based on a bibliometric analysis of the journal and an in-depth interview with the editor Prof. Leo Paul Dana about the journal, his academic and personal life. By using SCOPUS data, the analysis maps the knowledge produced and disseminated by the journal revealing the most cited papers and most prolific authors. By also presenting a keywords correlation analysis, the paper shows the main streams of research covered by the journal and their evolution. Although the objective of mapping the knowledge in WREMSD, this paper offers an example of application of a mixed method to bibliometric studies and methodological implications are discussed.